Gender differential impact of bereavement on health outcomes: evidence from the China Health and Retirement Longitudinal Study, 2011–2015 - Chen, Zhuo; Ying, Jiahui; Ingles, Justin; Zhang, Donglan; Rajbhandari-Thapa, Janani; Wang, Ruoxi; Emerson, Kerstin Gerst; Feng, Zhanchun (2020)
Background: Bereavement is the experience of an individual following the death of a person of significance to the individual, most often referring to the spouse. Increased morbidity, health care utilization, and mortality are known to be associated with bereavement. Given China’s growing population of older adults, there is a critical need to assess the health consequences of bereavement. Method: We use data from the China Health and Retirement Longitudinal Study to examine the impact of bereavement on mental health and quality of life among a sample of mid- and older-aged adults. We use propensity score matching to construct a matching sample and difference-in-differences method to estimate the impact of bereavement on mental health and self-assessed health. Results: We find bereavement is associated with increased depression symptoms among women (1.542 point or 0.229 standard deviations of Center for Epidemiologic Studies Depression (CES-D) 10 score) but not consistently for men over time. No statistically significant effect of bereavement on self-assessed health is found. Conclusions: Our results show a harmful impact of bereavement on mental health among older women in China and point to the need for a comprehensive policy on survivor benefits in China, particularly for rural older women.